2001
DOI: 10.1046/j.1365-2311.2001.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of latex and cardiac glycosides on survival and growth of first‐instar monarch butterfly larvae Danaus plexippus feeding on the sandhill milkweed Asclepias humistrata

Abstract: Summary1. A novel experimental method was developed to study negative physical and chemical effects of latex and cardiac glycosides on first‐instar monarch butterfly larvae in their natural environment in north central Florida. Forceps were used to nibble through the petioles of leaves of the sandhill milkweed Asclepias humistrata, mimicking the behaviour of mature monarch larvae. This notching cut off the supply of latex to the leaves without significantly reducing either their cardiac glycoside concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
168
4
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(182 citation statements)
references
References 40 publications
8
168
4
2
Order By: Relevance
“…There is a growing body of empirical literature that demonstrates that many chemical defences incur fitness costs, either through the costs of biosynthesis or acquisition (via sequestration or symbiosis) and storage. Such costs are often seen in reductions in growth, in adult size, in fecundity or have been directly measured in energetic terms (Cohen, 1985;Zalucki et al, 2001;Bowers & Collinge, 1992;Camara, 1997;Bjorkman & Larsson, 1991;Rowell-Rahier & Pasteels, 1986;Dobler & Rowell-Rahier, 1994;Grill & Moore, 1998), although we note that in some circumstances costs have not been detected (Bowers, 1988;Kearsley & Whitham, 1992).…”
Section: Be Enemies Not To Attack Them and They Have Usually Obtainementioning
confidence: 79%
“…There is a growing body of empirical literature that demonstrates that many chemical defences incur fitness costs, either through the costs of biosynthesis or acquisition (via sequestration or symbiosis) and storage. Such costs are often seen in reductions in growth, in adult size, in fecundity or have been directly measured in energetic terms (Cohen, 1985;Zalucki et al, 2001;Bowers & Collinge, 1992;Camara, 1997;Bjorkman & Larsson, 1991;Rowell-Rahier & Pasteels, 1986;Dobler & Rowell-Rahier, 1994;Grill & Moore, 1998), although we note that in some circumstances costs have not been detected (Bowers, 1988;Kearsley & Whitham, 1992).…”
Section: Be Enemies Not To Attack Them and They Have Usually Obtainementioning
confidence: 79%
“…Latex and cardenolides can each negatively impact specialist milkweed herbivores, including monarch butterflies (Zalucki and Malcolm 1999, Zalucki et al 2001, Agrawal 2004, Van Zandt and Agrawal 2004, Agrawal 2005, Agrawal et al 2012a, Agrawal et al 2014a), although we do not have information on their independent versus joint effects. Here we have shown that there are cardenolides in latex, but they are not concentrated compared to leaves (as is the case in other species; Seiber et al 1982, and residual latex may not contribute substantially to what we measure as ''foliar cardenolides''.…”
Section: Conclusion and Speculationmentioning
confidence: 99%
“…Three traits-cardenolides, latex, and trichomes-have been strongly implicated in providing milkweed resistance against herbivores. Each of these traits has been demonstrated to quantitatively affect the behavior (4, 5), performance (1,6,7), and abundance (8) of herbivores in the field. The resistance provided by these three traits occurs despite the fact that most milkweed herbivores are specialists and have adaptations to cope with each defense (4,5,9).…”
mentioning
confidence: 99%